2017
DOI: 10.1007/s40843-017-9077-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced carbon materials for flexible and wearable sensors

Abstract: Flexible and wearable sensors have drawn extensive concern due to their wide potential applications in wearable electronics and intelligent robots. Flexible sensors with high sensitivity, good flexibility, and excellent stability are highly desirable for monitoring human biomedical signals, movements and the environment. The active materials and the device structures are the keys to achieve high performance. Carbon nanomaterials, including carbon nanotubes (CNTs), graphene, carbon black and carbon nanofibers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(120 citation statements)
references
References 282 publications
(404 reference statements)
0
120
0
Order By: Relevance
“…However, the practical application of this type of sensors in smart textiles is restricted due to low flexibility, stretchability, and poor dynamic performance . Alternatively, they can be used in applications that require low strain range detection …”
Section: Textile‐based Strain Sensormentioning
confidence: 99%
“…However, the practical application of this type of sensors in smart textiles is restricted due to low flexibility, stretchability, and poor dynamic performance . Alternatively, they can be used in applications that require low strain range detection …”
Section: Textile‐based Strain Sensormentioning
confidence: 99%
“…Carbonization of natural materials is a promising strategy for obtaining carbon materials from sustainable resources [22][23][24]. Complete carbonization of cocklebur fruit, as demonstrated by TGA curve (Fig.…”
Section: Preparation and Characterization Of Carbon Materialsmentioning
confidence: 99%
“…Density functional theory calculations revealed that EDA effectively blocked the adsorption of oxidizing species (OH − ) and the oxidation of Cu seeds, which was attributed to a filling of the antibonding states accompanied by an increase of the electrostatic repulsion [151]. Graphene endows the soft electronics with outstanding reliability and long-term stability as well as high conductivity [12,25,26,28,152]. Especially, graphene oxide or reduced graphene oxide can provide an effective monolayer for protecting the inner metal atoms from corrosion [153].…”
Section: Monolayer Coatingsmentioning
confidence: 99%
“…These soft electronics enable the more approachable network of internet of things, and allow the future electronics to take more crucial roles in health monitoring, soft robotics, electronic skins and biological sensors [4][5][6][7]. Flexible and highly conductive conductors are playing a vital role in these advanced electronics, including wearable electronics [5,[8][9][10][11][12], stretchable transistors [13], ultrasensitive and selective non-enzymatic glucose detection [14], flexible solar cells [15], stretchable organic light-emitting diodes (LEDs) [16,17], biosensors or biomimetic sensors [6,18], actuators [19,20], energy harvesting devices [21][22][23][24][25][26][27][28] and so on. One way to realize these soft conductors needs intimate and robust integration of highly conductive metal nanomaterials with mechanically stretchable elastomers.…”
Section: Introductionmentioning
confidence: 99%